2021
DOI: 10.1101/2021.08.21.457238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bifurcating Neurons In The Anterior Thalamic Nuclei

Abstract: The anterior thalamic nuclei (ATN) form a nodal point within a hippocampal-cingulate-diencephalic memory system. ATN projections to different brain structures are conventionally viewed as distinct, but ATN neurons may send collaterals to multiple structures. The anteromedial subregion (AM) is the primary source of efferents to the medial prefrontal cortex (mPFC). Using a dual-retrograde neurotracer strategy, we discovered bifurcating AM neurons for tracers placed in the mPFC when paired with other regions. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 55 publications
1
10
1
Order By: Relevance
“…Finding an appreciable proportion of neurons in nucleus reuniens that project to both medial prefrontal cortex and the hippocampal formation ($36%) appears inconsistent with the 5%-10% previously reported for the same termination pairings (Hoover & Vertes, 2012;Varela et al, 2014). Furthermore, it had been observed that considerably more double-labelled cells are present in the ventral hippocampal formation (Hoover & Vertes, 2012), something not described in the later study (Pei et al, 2021). In addition, Pei et al (2021) reported appreciable populations of double-labelled cells in both the anteromedial nucleus ($20%) and nucleus reuniens (26%) for the medial prefrontal cortex/retrosplenial cortex pairing (Pei et al, 2021), yet this same combination gave proportions closer to zero in the present study.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Finding an appreciable proportion of neurons in nucleus reuniens that project to both medial prefrontal cortex and the hippocampal formation ($36%) appears inconsistent with the 5%-10% previously reported for the same termination pairings (Hoover & Vertes, 2012;Varela et al, 2014). Furthermore, it had been observed that considerably more double-labelled cells are present in the ventral hippocampal formation (Hoover & Vertes, 2012), something not described in the later study (Pei et al, 2021). In addition, Pei et al (2021) reported appreciable populations of double-labelled cells in both the anteromedial nucleus ($20%) and nucleus reuniens (26%) for the medial prefrontal cortex/retrosplenial cortex pairing (Pei et al, 2021), yet this same combination gave proportions closer to zero in the present study.…”
Section: Discussioncontrasting
confidence: 93%
“…A largely complementary study also investigated collateral cortical projections from the anteromedial nucleus and nucleus reuniens (Pei et al, 2021). Much of their focus was on whether cortical collaterals reach the hippocampal formation (Pei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations